Soil mechanics concepts and applications - Powrie, William (E & FN Spon, 1997)
The aim of this book is to encourage students to develop an understanding of the fundamentals of soil mechanics. It builds a robust and adaptable framework of ideas to support and accommodate the more complex problems and analytical procedure that confront the practising geotechnical engineer.